2020
DOI: 10.3390/ani10071138
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Housing Environment on the Immune System in Chickens: A Review

Abstract: During their lifespan, chickens are confronted with a wide range of acute and chronic stressors in their housing environment that may threaten their welfare and health by modulating the immune system. Especially chronic stressful conditions can exceed the individual’s allostatic load, with negative consequences for immunity. A fully functional immune system is mandatory for health and welfare and, consequently, also for high productivity and safe animal products. This review provides a comprehensive ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 204 publications
0
45
0
1
Order By: Relevance
“…In addition, cytokines are the predominant mediators of inflammation with an essential role in mediating the inflammatory response during heat stress in living organisms [ 38 ]. Several studies have confirmed the relationship between the inflammatory response of the immune organs and the expression of inflammatory cytokines [ 5 ]. The most effective role played by TNF-α, as the most important cytokine, is related to its potent cytoprotective and antioxidant activity in response to injuries [ 5 , 46 ], and activating lymphocytes and neutrophils to produce the other cytokines [ 47 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, cytokines are the predominant mediators of inflammation with an essential role in mediating the inflammatory response during heat stress in living organisms [ 38 ]. Several studies have confirmed the relationship between the inflammatory response of the immune organs and the expression of inflammatory cytokines [ 5 ]. The most effective role played by TNF-α, as the most important cytokine, is related to its potent cytoprotective and antioxidant activity in response to injuries [ 5 , 46 ], and activating lymphocytes and neutrophils to produce the other cytokines [ 47 ].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have confirmed the relationship between the inflammatory response of the immune organs and the expression of inflammatory cytokines [ 5 ]. The most effective role played by TNF-α, as the most important cytokine, is related to its potent cytoprotective and antioxidant activity in response to injuries [ 5 , 46 ], and activating lymphocytes and neutrophils to produce the other cytokines [ 47 ]. The TNF-α was down-regulated in the AST80 treatment but not in the AST40 or AST20 treatments.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Air quality, especially increased ammonia (NH 3 ) and hydrogen sulfide (H 2 S) concentrations, is an important factor influencing poultry health and bird performance, including feed efficiency, growth rate, carcass quality, and susceptibility to diseases. Indeed, harmful concentrations of NH 3 and H 2 S can suppress/dampen adaptive immune responses [ 239 ].…”
Section: Effect Of Various Stress Factors On Nf-κb Expression and mentioning
confidence: 99%